The interaction of early life experiences with COMT val158met affects anxiety sensitivity. (25th October 2013) - Baumann, C.; Klauke, B.; Weber, H.; Domschke, K.; Zwanzger, P.; Pauli, P.; Deckert, J.; Reif, A.
Abstract : The pathogenesis of anxiety disorders is considered to be multifactorial with a complex interaction of genetic factors and individual environmental factors. Therefore, the aim of this study was to examine gene‐by‐environment interactions of the genes coding for catechol‐ O ‐methyltransferase (COMT) and monoamine oxidase A (MAOA) with life events on measures related to anxiety. A sample of healthy subjects ( N = 782; thereof 531 women; mean age M = 24.79, SD = 6.02) was genotyped for COMT rs4680 and MAOA ‐uVNTR (upstream variable number of tandem repeats), and was assessed for childhood adversities [Childhood Trauma Questionnaire (CTQ)], anxiety sensitivity [Anxiety Sensitivity Index (ASI)] and anxious apprehension [Penn State Worry Questionnaire (PSWQ)]. Main and interaction effects of genotype, environment and gender on measures related to anxiety were assessed by means of regression analyses. Association analysis showed no main gene effect on either questionnaire score. A significant interactive effect of childhood adversities and COMT genotype was observed: Homozygosity for the low‐active met allele and high CTQ scores was associated with a significant increment of explained ASI variance [ R 2 = 0.040, false discovery rate (FDR) corrected P = 0.04]. A borderline interactive effect with respect to MAOA ‐uVNTR was restricted to the male subgroup. Carriers of the low‐active MAOA allele who reported more aversive experiences in childhood exhibited a trend for enhanced anxious apprehension ( R 2 = 0.077, FDR corrected P = 0.10). Early aversive life experiences therefore might increase the vulnerability to anxiety disorders in the presence of homozygosity for the COMT 158met allele or low‐active MAOA ‐uVNTR alleles . Abstract : The aim of this study was to examine gene‐by‐environment interactions of the genes coding for catechol‐ O ‐methyltransferase ( COMT ) and monoamine oxidase A ( MAOA ) with life events on measures related to anxiety in a sample of healthy adults. Association analysis showed no main gene effect. A significant interactive effect of childhood adversities and COMT genotype was observed. Homozygosity for the low‐active met allele and high CTQ scores was associated with a significant increment of explained ASI variance. A borderline interactive effect with respect to MAOA ‐uVNTR was restricted to the male subgroup. Carriers of the low‐active MAOA allele who reported more aversive experiences in childhood exhibited a trend for enhanced anxious apprehension.